Analisis Sistem Penyimpanan Dan Prosedur Temu Kembali Arsip Dinamis di PT Artojoyo Langgeng Jaya Abadi (JH Tech Sidoarjo) - Melinda Resti Susanti; Durinda Puspasari (Universitas Negeri Surabaya, 2020)
The purpose of this study was to analyze the storage system and dynamic archive retrieval procedure at PT Artojoyo Langgeng Jaya Abadi (JH Tech Sidoarjo). This type of research is a descriptive study using a qualitative approach. The subjects of this study were 3 administrative section employees. Data collection techniques used by researchers are interviews. In this study, researchers used a source triangulation method which conducted interviews with the Head of Administration of PT Artojoyo Langgeng Jaya Abadi (JH Tech Sidoarjo). The data analysis technique used by researchers is the analysis of Miles and Huberman data models consisting of data reduction, data display and conclusion drawing / verification. The results of research conducted indicate that the storage system is a date system. Storage system is done by date with a manual system but the storage system is not good, because it is not carried out in the order of storage steps according to the experts so that it results in an accumulation of archives and is not neatly organized and difficult to recover the records. Records retrieval procedure uses only one tool to rediscover the archive, which is an agenda book where employees must search the required archives one by one on the date stated so that it takes a long time and hinders the employee's performance in handling the records. The time needed is far from the standard search time, which is approximately 1 (one) minute per archive, while at PT Artojoyo Langgeng Jaya Abadi (JH Tech Sidoarjo) to find one archive takes 5 to 10 minutes. Barriers or problems often occur in the storage process that is confusion employees put the archive on the shelf because the storage space is narrow with increasing records. So there is a need for other tools, namely the loan card archive so that it can maximize the work of employees in the storage system and the recovery of records.Keywords: Storage System; Archive Retrival.